Holmes Tremor Secondary to a Stabbing Lesion in the Midbrain - Rubens Gisbert Cury; Egberto Reis Barbosa; Christian Freitas; Luis Filipe de Souza Godoy; Wellingson Silva Paiva (Tremor and Other Hyperkinetic Movements, 2017)
Background: The development of Holmes tremor (HT) after a direct lesion of the midbrain has rarely been reported in the literature, although several etiologies have been linked with HT, such as stroke, brainstem tumors, multiple sclerosis, head trauma, or infections. Phenomenology Shown: A 31-year-old male, having been stabbed in the right eye, presented with a rest and action tremor in the left upper limb associated with left hemiparesis with corresponding post-contrast volumetric magnetic resonance imaging T1 with sagittal oblique reformation showing the knife trajectory reaching the right midbrain. Educational Value: Despite the rarity of the etiology of HT in the present case, clinicians working with persons with brain injuries should be aware of this type of situation.